Plasma Total Homocysteine and its Relationship with Cardiovascular Disease - Bryan, Stephanie; Parasher, Raju; Cahil, Terrence; Zipp, P.T. Genevieve Pinto (Journal of Nutritional Therapeutics, 2013)
Physical inactivity, overweight, and obesity are serious issues plaguing the American public. The extent to which regular yoga participation may be associated with the adoption and maintenance of health enhancing behaviors necessitates further investigation. Through a mixed method of inquiry, this study investigated the exercise and eating habits of adults who participate in yoga on a regular basis exploring facets of mindful eating, exercise habits, and body mass index. Survey packets were distributed across seven yoga studios and fitness facilities in central New Jersey; 87 adults with a mean age of 47 years self-selected to participate. Quantitative and qualitative data were collected including a Mindful Eating Questionnaire, a 7-Day Physical Activity Recall, height and weight, yoga tenure recorded in months/years of consistent yoga participation, and average daily fruit and vegetable intake. Results showed that mindful eating was inversely correlated with Body Mass Index (BMI) and that 72% of the yoga participants had a BMI of 24.9 or less, placing them in the normal weight category. A significant difference existed in mindful eating score relative to yoga tenure and vegetable and fruit intake relative to yoga tenure. Participants reported a mean of 239 minutes of weekly exercise other than yoga participation. Qualitative data were collected through two open-ended questions to ascertain the participants’ perceptions of yoga and their health-related behaviors; the data revealed that 87% of participants felt yoga enhanced their exercise adherence and 91% reported yoga promoted the adoption of positive health habits. The results suggest that yoga participation is associated with mindful eating and the adoption and maintenance of other positive health-related outcomes such as regular physical activity and weight management.